Mechatronic system of automatic and manual differential lock control vehicle turnig - Kucera, Pavel; Pistek, Vaclav (2016 17th International Conference on Mechatronics - Mechatronika (ME), 2016)
This article deals with the creation of control algorithm for locking differential of the truck. This algorithm is based on assumptions of the ZF ADM - Automatic Drive-Train Management system and it is created using software Simulink-Stateflow. The article describes the function of algorithm and its application to the computational model of vehicle with 8×8 drive. In conclusion, a simulation of driving manoeuvres is done to verify the functionality of the assembled control algorithm of the differential.